AS INIQUIDADES EM SAÚDE: UMA ANÁLISE DOS DETERMINANTES RELATIVOS AO ADOECIMENTO POR TUBERCULOSE NO MUNICÍPIO DE GUARAPUAVA NO PERÍODO DE 2005 A 2015 - Klosowski, Luiz Augusto (2017)
Tuberculosis is one of the oldest diseases of mankind, carries the weight of a historical stigma and continues to be one of the great challenges of Public Health. It is notorious that the population does not have the perception that tuberculosis is a global public health problem and still thousands of people become ill and die due to the disease and its complications. Thus, the objective was to analyze the social representations of people with tuberculosis, as well as the spatial distribution of the cases of the disease in the city of Guarapuava, state of Paraná, relating them to the level of schooling of the notified patients. Also, the existence of a spatial distribution pattern of the incidence rate of the disease in the city, as well as the behavior of the diagnosed cases of tuberculosis in the city districts. This is a study that used the mixed method, that is qualitative and quantitative, considering the objectives is exploratory-descriptive, applied nature and documentary analysis. Regarding the method of data collection, secondary sources were used. The study describes 316 cases of TB notified during the 10 years evaluated, with incidence ranging from 0.101/ 1.000hab to 0.288/ 1.000hab. It has not been demonstrated a spatial pattern of distribution of the disease in the city, although a large number of cases being reported in the suburbs of the city. A greater number of cases was also notified in people of lower educational level and age group that corresponds to the economically active age. So, we suggest such groups that should be a priority of the Government in public policy to consider in the process of coping strategies of tuberculosis so that the vulnerability to illness from being modified. Although Guarapuava present a relatively controlled situation of tuberculosis, the iniquities concerning this disease need greater attention, in order to give people a situation worthy of life, which is an important step to reach in 2035 the goal proposed by the who, which is the Elimination of tuberculosis in the country.